Catch the spirit : teen volunteers tell how they made a difference : stories of inspiration from 20 remarkable recipients of the Prudential Spirit of Community Award - Perry, Susan K., 1946- (New York : F. Watts, 2000)
Individual teenagers relate their experiences in various types of volunteer activities.
Includes bibliographical references (p. 189-190).
Books for the Teen Age (NYPL).
School Library Journal.
Wilson's Senior High School.
Young Adult
Keywords: Teenage volunteers in social service -- United States -- Interviews -- Juvenile literature; Voluntarism -- United States -- Juvenile literature; Teenage volunteers in social service; Voluntarism; Volunteer work